Relationship of nutritional status, calcium intake and stress with pre-menstrual syndrome in UHAMKA nutrition student - Ananda Afifa Kurnia Mahardika (ARGIPA (Arsip Gizi dan Pangan), 2020)
Pre-menstrual syndrome (PMS) is a set of psychic and physical symptoms experienced by women of childbearing age between 7-10 days before menstruation. This study used cross-sectional design with quantitative approach. Sampling was done by simple random sampling method. This study used primary data of semi-quantitative food frequency interview, Shortened Premenstrual Assessment Form (SPAF) and perceived stress scale questionnaire. The result of this study, it can be concluded that most of UHAMKA Nutrition Students have a pre-menstrual syndrome, high stress levels, and adequate calcium intake. Statistical test results showed that there was a relationship between stress with the premenstrual syndrome, while calcium intake and nutrional status showed no relationship.